An Improved Fast Mode Decision Method for H.264/AVC Intracoding - Abderrahmane Elyousfi (Advances in Multimedia)
An improved fast and efficient mode decision method for H.264/AVC intracoding is proposed, which is based on the analysis of the gravity center method and more efficient mode selection. In contrast to the fast mode decision method where the intramodes are determined by the gravity center of the block, the mass center vector is computed for the block and the subblocks formed by the proposed subsampling techniques. This method is able to determine all correlation directions of the block that correspond to the intraprediction mode directions of the H.264/AVC. On this basis, only a small number of intraprediction modes are chosen as the best modes for rate-distortion optimization (RDO) calculation. Different video sequences are used to test the performance of the proposed method. Experimental results reveal the significant computational savings achieved with slight peak signal-to-noise ratio (PSNR) degradation and bit-rate increase.